Slow dynamics in debris-covered and rock glaciers in Hofsdalur, Tröllaskagi Peninsula (northern Iceland) - Campos, Néstor; Zamorano León, José Javier; Tanarro García, Luis Miguel; Palacios Estremera, David (Geomorphology, 2019)
The results of previous work on the dynamics of the debris-covered and rock glaciers in Tröllaskagi are contradictory. To improve our knowledge of these dynamics and determine the origin and evolution of these landforms, we analyzed two case studies located in the Hofsdalur Valley: the Hofsjökull debris-covered glacier and the Júllogil rock glacier, using digital photogrammetry combined with GIS techniques. Our most accurate results were obtained for the period 1980–1994 as follows: for the Hofsjökull debris-covered glacier a mean block displacement velocity of 0.22 m yr−1, a block elevation difference of −0.36 m and a horizontal displacement of linear ridges of 0.21 m yr−1; for the Júllogil rock glacier a mean block displacement velocity of 0.15 m yr−1, a block elevation difference of −0.63 m and a horizontal displacement of linear ridges of 0.16 m yr−1. The limits of these glaciers remained stable for ~70 years, from 1946 to 2017. All our data support the fact that these landforms are stable, and having lost their ice accumulation sources, their dynamics are fundamentally related to subsidence processes. Therefore, they are relict landforms whose origin seems to be related to paraglacial processes after rapid deglaciation of the valleys, and their stagnated ice is preserved, as it is above the permafrost level. Ministerio de Economía, Comercio y Empresa (España) Nils Mobility Program Depto. de Geografía Fac. de Geografía e Historia TRUE pub